Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Pajak Pribadi di Kota Batam - Rudiman, Rudiman; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2023)
The purpose of this study was to find out whether tax sanctions, taxpayer awareness and tax knowledge affect personal taxpayer compliance in the city of Batam. In this study, researchers used a questionnaire method. The population in this study is the number of taxpayers who report at KPP Pratama Batam Selatan. Using the Slovin formula, this study's sample represents 10 percent of the total population. This investigation utilises primary data. This study's data collection method was a questionnaire. This investigation employs the Statistical Package for the Social Sciences (SPSS) for data analysis. With a Tcount of 3.068 > Ttable of 1.98489 and a Sig. 0.003 0.05, tax sanctions on personal taxpayer compliance are obtained with a Tcount of 3.068 > Ttable of 1.98489. This indicates that Ha is approved and Ho is rejected. Therefore, it can be partially concluded that tax sanctions have a substantial impact on taxpayer compliance in the city of Batam. The Tcount value is 1.676 Ttable 1.98489, and the Sig. is 0.097 > 0.05, based on the research findings regarding taxpayer awareness of compliance. This indicates that Ho is recognised while Ha is not. Therefore, it can be partially concluded that taxpayer awareness has no significant effect on taxpayer compliance in Batam. Based on the research results of tax knowledge on taxpayer compliance, the Tcount value is 0.817 <Ttable 1.98489 and the Sig. 0.416 > 0.05. This means that Ho is accepted and Ha is rejected. So it can be concluded partially that tax knowledge has no significant effect on taxpayer compliance in the city of Batam. Based on the research results of tax sanctions, taxpayer awareness and knowledge of taxation on taxpayer compliance, the Fcount value is 23.074 > Ftable 2.7 and the value of Sig. of 0.000 <0.05. This means that Ho is rejected and Ha is accepted. So it can be concluded that simultaneously tax sanctions, taxpayer awareness and tax knowledge have a significant effect on taxpayer compliance in the city of Batam.